The Onset Time of the Ownership Sensation in the Moving Rubber Hand Illusion - Kalckert, Andreas; Ehrsson, H. H. (Frontiers in Psychology, 2017)
The rubber hand illusion is a perceptual illusion whereby a model hand is perceived as part of one’s own body. This illusion has been extensively studied, but little is known about the temporal evolution of this perceptual phenomenon, i.e., how long it takes until participants start to experience ownership over the model hand. In the present study, we investigated a version of the rubber hand experiment based on finger movements and measured the average onset time in active and passive movement conditions. This comparison enabled us to further explore the possible role of intentions and motor control processes that are only present in the active movement condition. The results from a large group of healthy participants (n=117) showed that the illusion of ownership took approximately 23 seconds to emerge (active: 22.8; passive: 23.2). The 90th percentile occurs in both conditions within approximately 50 seconds (active: 50; passive: 50.6); therefore, most participants experience the illusion within the first minute. We found indirect evidence of a facilitatory effect of active movements compared to passive movements, and we discuss these results in the context of our current understanding of the processes underlying the moving rubber hand illusion.